Cenários da violência: análise estético-narrativa do telejornal policial Barra Pesada - Morales, Luciana Pinho (2014)
This dissertation analyses the aesthetic dimension of narratives about urban violence presented by the police program “Barra Pesada” in the state of Ceará, Brazil, aiming to understand the symbolic repertoires and the classification systems conveyed in the images, words and sounds of this newscast. The investigation of a recorded program sample, related to one-year period (June 2012 to July 2013), allowed to verify how the violent events and their protagonists are presented by the media, discussing the role of television in the social construction process of the urban violence phenomenon. To analyze text and motion pictures was utilized a combination of researching techniques, known as “Ethnography of the Screen”,supported by specific anthropological research procedures, such as the long immersion on the field, the tool of field diary and the resource of extenuating systematic observation; in cinematography critic; and in discourse analysis. These techniques allowed the analysis of a collection of images, words and sounds, and their symbolic meanings conveyed by the TV program studied, maintaining a constant dialogue between the analysis of the verbal and the nonverbal. In this research, it was possible verify that the media coverage not only describes the actions related to urban violence, but it’s also an integrant part of the phenomenon and the social dramas that are developed as a result of the news. It was observed that the program “Barra Pesada” look for legitimation to act, not only as a collaborator of formal control agencies, but as an alternative mechanism for social control and justice, reaffirming moral values, offering recipes for social cohesion and proposing solutions to contain the advance of urban violence and public insecurity.